2023
DOI: 10.3389/fonc.2022.1068094
|View full text |Cite|
|
Sign up to set email alerts
|

High expression level of the FTH1 gene is associated with poor prognosis in children with non-M3 acute myeloid leukemia

Abstract: Acute myelogenous leukemia (AML) is a disease that severely affects the physical health of children. Thus, we aimed to identify biomarkers associated with AML prognosis in children. Using transcriptomics on an mRNA dataset from 27 children with non-M3 AML, we selected genes from among those with the top 5000 median absolute deviation (MAD) values for subsequent analysis which showed that two modules were associated with AML risk groups. Thus, enrichment analysis was performed using genes from these modules. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
1
1
0
Order By: Relevance
“…This is supported by other studies, which have also shown that higher expression of SLC7A11, GPX4 and LPCAT3 is associated with a worse prognosis in AML, while overexpression of TFRC, which encodes the transferrin receptor, was found to protect cells against ferroptosis [113,114]. In children with non-M3 AML, FTH1 expression is associated with a poor prognosis and is upregulated during the proliferation of AML cell lines [115]. Numerous publications have identified other ferroptosis-related gene signatures, eluding to the relevance of ferroptosis in AML but also indicating the dataset used and other factors may contribute to what genes can be used to predict both prognosis and ferroptosis-sensitivity in AML [116][117][118][119][120][121].…”
Section: Acute Myeloid Leukaemiasupporting
confidence: 79%
“…This is supported by other studies, which have also shown that higher expression of SLC7A11, GPX4 and LPCAT3 is associated with a worse prognosis in AML, while overexpression of TFRC, which encodes the transferrin receptor, was found to protect cells against ferroptosis [113,114]. In children with non-M3 AML, FTH1 expression is associated with a poor prognosis and is upregulated during the proliferation of AML cell lines [115]. Numerous publications have identified other ferroptosis-related gene signatures, eluding to the relevance of ferroptosis in AML but also indicating the dataset used and other factors may contribute to what genes can be used to predict both prognosis and ferroptosis-sensitivity in AML [116][117][118][119][120][121].…”
Section: Acute Myeloid Leukaemiasupporting
confidence: 79%
“…12 In children with non-M3 acute myeloid leukemia, high levels of FTH1 have been shown to promote the proliferation and inhibit the ferroptosis of leukemia cells, suggesting that FTH1 is a risk factor and treatment target in non-M3 acute myeloid leukemia. 13 Furthermore, Mao et al have found that the level of ferroptosis gene FTH1 is significantly relevant to the survival of HNSCC samples, and Tanshinone IIA (TanIIA) is capable of inhibiting cell survival and the invasiveness of Fadu cells (a human hypopharynx squamous carcinoma cell line), via suppressing FTH1. 14 In contrast, interaction between FTH1 and PRDX6 in cancer cells results in a less invasive phenotype.…”
mentioning
confidence: 99%